INFLUENCE OF FAMILY TYPES ON ADOLESCENT PSYCHO-SOCIAL PROBLEM BEHAVIOURS AMONG HIGH SCHOOL STUDENTS IN ORIADE LOCAL GOVERNMENT AREA, OSUN STATE, NIGERIA. - Yejide Olulani Alebiosu (Universitas Pendidikan Indonesia, 2024)
The study investigated the influence of family types on adolescent psycho-social problem behaviours among high school adolescents in Oriade, Osun state, Nigeria. Study adopted the descriptive survey design. The population of the study consisted of high school adolescents from intact, single and step families. The study adopted the simple random technique to select ten secondary schools in Oriade. In each of these schools, thirty (30) adolescents (10 from each family type) were selected using stratified sampling technique, totalling three hundred respondents. Four hypotheses were raised in the study. A constructed instrument with reliability coefficient of 0.76, titled Family Types and Adolescents Psycho-social Problem Behaviour Questionnaire (FTAP2BQ) was used to collect data for the study. Data collected were analysed using inferential statistics of t-test and regression analyses. Findings showed: no significant difference across family type in adolescent sexual abuse behaviour (F = 1.963, p0.05); no significant difference in adolescent cyber addiction behaviour across family type (F = 1.166, p0.05); significant gender difference in the influence of family type on adolescent problem behaviour of sexual abuse (t = 2.593, p0.05); and no significant age differences in the influence of family type on adolescent problem behaviour of cyber addiction (F = 0.404, p0.05). Recommendations included that parents in all family types should: ensure high-quality physical presence; monitor internet surfing activities of their adolescents.